Zagubieni w labiryncie: trzy współczesne obrazy filmowe – trzy przestrzenie zagubienia (szkic interpretacyjny) - Sieńkowska, Karolina (Załącznik Kulturoznawczy, 2014)
The complexity of labirynth’s construction is inseparably connected with the complexity of its symbolical meanings. For centuries mankind − driven by various feelings − has given labirynth figurative meanings. Poetry, painting and all other kinds of art have shown the world as a maze. Cinema as well. This work is an attempt of following the labirynth motive in chosen film works. In each of the cases a labirynth will be discussed in the context of its relations with a man. Researcher focuses mainly on the way the labirynth affects the people inside him